Understanding the Mechanism of Dysglycemia in a Fanconi-Bickel Syndrome Patient - Sharari, Sanaa; Aouida, Mustapha; Mohammed, Idris; Haris, Basma; Bhat, Ajaz Ahmad; Hawari, Iman; Nisar, Sabah; Pavlovski, Igor; Biswas, Kabir H.; Syed, Najeeb; Maacha, Selma; Grivel, Jean-Charles; et al. (Frontiers in Endocrinology, 2022)
Fanconi–Bickel Syndrome (FBS) is a rare disorder of carbohydrate metabolism that is characterized mainly by the accumulation of glycogen in the liver and kidney. It is inherited as an autosomal recessive disorder caused by mutations in the SLC2A2 gene, which encodes for GLUT2. Patients with FBS have dysglycemia but the molecular mechanisms of dysglycemia are still not clearly understood. Therfore we aimed to understand the underlying molecular mechanisms of dysglycemia in a patient with FBS. Genomic DNA was isolated from a peripheral blood sample and analyzed by whole genome and sanger sequencing. CRISPR-Cas9 was used to introduce a mutation that mimics the patient’s mutation in a human kidney cell line expressing GLUT2 (HEK293T). Mutant cells were used for molecular analysis to investigate the effects of the mutation on the expression and function of GLUT2, as well as the expression of other genes implicated in dysglycemia. The patient was found to have a homozygous nonsense mutation (c.901C>T, R301X) in the SLC2A2 gene. CRISPR-Cas9 successfully mimicked the patient’s mutation in HEK293T cells. The mutant cells showed overexpression of a dysfunctional GLUT2 protein, resulting in reduced glucose release activity and enhanced intracellular glucose accumulation. In addition, other glucose transporters (SGLT1 and SGLT2 in the kidney) were found to be induced in the mutant cells. These findings suggest the last loops (9-12) of GLUT2 are essential for glucose transport activity, and indicate that GLUT2 dysfunction is associated with dysglycemia in FBS.